Taxonomy of stingless bee in Malaysia - Md Subahai, Nazatul Syafiqah (2016)
The objectives for this study were to identify the stingless bee species in Malaysia, to construct key for stingless bee species in Malaysia and to describe each species of stingless bee. Sampling was conducted in Malaysia Genome Institute, Bangi. Five to ten individuals of stingless bees were collected from the nest entrance by using a sweep net. Fresh samples were inserted to the killing jar containing ethyl acetate to kill the stingless bee. After that, the specimens were transferred into glass container containing 70% alcohol for preservation purposes and labeled before pinning in the laboratory. Then, the specimens were dried. From this study, a total of eight genus and 16 species were obtained. The key to genus was constructed and each species was described in details.